Gender Discrimination in Children’s Folktales: A Special Study of Ashraf Sabohi’s Stories - Dr. Tahir Nawaz,; Dr. Ghulam Farida,; Dr. Aqlima Naz,; Dr. Maria Termezi, (Al-Qanṭara, 2024)
Children’s folktales are one of the most popular genres of the Urdu literature. There are large numbers of magazines and periodicals on children's literature in Urdu. A large number of Urdu books are also published in children's literature. Many writers became popular for their stories and folktales in children's literature. Ashraf Sabohi is one of those who wrote stories for children and became popular. Folktales and stories are also considered a big part of early childhood education which develops the children’s behavior, thinking, and creativeness. So children's literature must be unbiased and without gender discrimination. When we critically analyzed Ashraf Sabohi’s folktales and stories written for children, there were serious issues regarding bias and gender discrimination. The serious question is whether either these folktales or short stories written by Ashraf Sabohi are suitable for early childhood education. This article is about gender discrimination in children’s folktales about the special study of Ashraf Sabohi’s stories a well-known writer of Urdu literature.